2021
DOI: 10.1002/csc2.20385
|View full text |Cite
|
Sign up to set email alerts
|

Floret site utilization and reproductive tiller number are primary components of grain yield in intermediate wheatgrass spaced plants

Abstract: Perennial plants provide extensive environmental services and increasing their prevalence on the agricultural landscape is one way to improve sustainability. Direct domestication of intermediate wheatgrass [Thinopyrum intermedium; (Host) Barkworth & D.R. Dewey] as a perennial grain crop is underway, and selection has focused primarily on improving seed size and grain yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 70 publications
(165 reference statements)
3
58
1
Order By: Relevance
“…If spike length is already routinely collected, spike emergence may be an easier method for assessing flowering time, but caution should be taken to measure it around 50% emergence so that a linear relationship exists between the two events. We previously reported that the two measures of flowering time appear to have a slightly different influence on grain yield in spaced plants ( Altendorf et al 2020 ), but no QTL regions detected in the present study appeared to be completely unique to one trait or the other.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…If spike length is already routinely collected, spike emergence may be an easier method for assessing flowering time, but caution should be taken to measure it around 50% emergence so that a linear relationship exists between the two events. We previously reported that the two measures of flowering time appear to have a slightly different influence on grain yield in spaced plants ( Altendorf et al 2020 ), but no QTL regions detected in the present study appeared to be completely unique to one trait or the other.…”
Section: Discussioncontrasting
confidence: 57%
“…Because an initial linear model analysis across environments revealed highly significant interactions, we analyzed all unique year by location combinations ( n = 4; environments hereafter) separately. This decision was further supported by differences in plant age between 2017 and 2018, as well as major differences in climate and GDD accumulation between STP and TLI, and a severe drought in 2018 at TLI ( Altendorf et al 2020 ). Parental means were calculated and plotted alongside emmeans for progeny genotypes using ggplot2 ( Wickham 2016 ).…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations